Design Thinking and Bricolage for Frugal Innovations during Crisis - Oly Mishra (Journal of Innovation Management, 2021)
The rapid spread of COVID-19has created resource-constraints. This study focuses on the application of design thinking in frugal innovations by social entrepreneurs to face the challenges during the COVID-19 pandemic. It discusses the case of an Indian social entrepreneur who essentially provides solutions for menstrual health and hygiene to unprivileged and rural women in India. When faced with the COVID-19 pandemic, the social entrepreneur re-purposed the manufacturing process and implemented bricolage to produce masks which were the need of the hour. The manufacture of masks was a frugal innovation due to the resource constraints during the pandemic. The research paper is qualitative, and it follows an inductive case study approach. The implementation of design thinking in frugally innovating is established through the content analysis of the interviews of the social entrepreneur and her team members. It presents practical implications of design-thinking for frugal innovations by social entrepreneurs in adversity.